ANALISIS KETERAMPILAN MENGAJAR CALON GURU MATEMATIKA PADA MATA KULIAH PEMBELAJARAN MICRO - Inayah, Sarah; Herlina, Sari (SIGMA DIDAKTIKA: Jurnal Pendidikan Matematika, 2021)
The main task of the LPTK is to produce high quality teachers. Those who will work in various educational units are prepared to be able to master the competence of teachers. In the teaching and learning process, the teacher plays a role as a director as well as an actor and is a very dominant factor in determining the success of the teaching and learning process in the classroom. Teachers' teaching skills and students' learning motivation are strongly correlated with partial or simultaneous learning outcomes. The Mathematics Education study program at the Faculty of Teacher Training and Education, Suryakancana University has the responsibility to produce skilled teachers in teaching in order to improve student learning outcomes. To be able to carry out these responsibilities through an integrated debriefing process in various courses, initial data is needed. The data contains an overview of the teaching skills of prospective mathematics teachers. Through this data, it can then be considered what steps must be taken to improve it as well as which skills must be improved again. Based on the results of the analysis obtained data that the teaching skills of prospective mathematics teachers in micro learning courses are in good criteria. However, improvements are needed in improving students' skills in managing classes